2020
DOI: 10.7458/spp20209417249
|View full text |Cite
|
Sign up to set email alerts
|

La integración de los venezolanos en Colombia: discurso de líderes inmigrantes en Bogotá y Cúcuta

Abstract: Producto de la crisis que enfrenta Venezuela, miles de ciudadanos venezolanos han ingresado a Colombia; movimiento migratorio que supone una serie de desafíos tanto para el gobierno como para la sociedad civil. El presente artículo analiza la configuración del imaginario social de la integración de los inmigrantes venezolanos, a partir de entrevistas realizadas a ocho líderes inmigrantes radicados en las ciudades de Bogotá y Cúcuta. El imaginario se analiza desde los conceptos axiales de la obra de M. A. Baeza… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0
4

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 0 publications
0
4
0
4
Order By: Relevance
“…Previous sociological studies, such as those of Doocy et al. (2019) and Aliaga Sáez et al. (2020) , have been able to document how the political, social and economic crisis in Venezuela has produced a massive exodus of more than three million Venezuelans to other countries of the world.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous sociological studies, such as those of Doocy et al. (2019) and Aliaga Sáez et al. (2020) , have been able to document how the political, social and economic crisis in Venezuela has produced a massive exodus of more than three million Venezuelans to other countries of the world.…”
Section: Introductionmentioning
confidence: 99%
“…This large number of immigrants in Colombian territory has generated different types of social conflicts, bearing in mind that Colombia does not have a developed economy; therefore, it was not prepared for this type of large-scale social interactions; In this way, Colombia faces the greatest international immigration to its country in its entire history, further deepening its own social and economic problems ( Aliaga Sáez et al. (2020) ; Martínez Moya, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…As can be seen, while always dealing with social issues, different categories of analysis are identified. For example, the group of sociologists work imaginary (imaginarios) (for example, Aliaga, F. 2008aAliaga, F. , 2008bAliaga, F. , 2012, community (comunidad) (for example, Acosta, C. et al 2019 and Urra, M. 2018b) inclusion or integration (integración) (Aliaga, F. 2008b(Aliaga, F. , 2012(Aliaga, F. and 2020. The group of other professionals works on categories such as resistance (resistencias) (Idrobo, J. , 2018 and 2020a) rights (derechos) (Añaños, K., and Hernández, B.…”
Section: -Resultsmentioning
confidence: 99%
“…These policies include foreign degrees validation, public employment services, training, access to credit, information campaigns on migration policies, social assistance, and policies promoting positive attitudes toward migrants. Abundant evidence has shown that these policies contribute to a faster and better assimilation process of migrants, with benefits that extend to the whole community (Allen, Ruiz, and Vargas-Silva 2022;Bauer, Lofstrom, and Zimmermann 2000;Beerli et al 2021;Fischer, Martin, and Straubhaar 2021;Ilahi 1999;Lowe et al 2022;McAuliffe and Khadria 2020;Sáez, et al 2020). Moreover, the support for integration policies is larger among people who have more social contact with migrants (Bauer, Lofstrom, and Zimmermann 2000;Boateng et al 2021;Clayton, Ferwerda, and Horiuchi 2021;Schneider 2008).…”
Section: Discussionmentioning
confidence: 99%